The Effect of Corporate Governance and Firm Performance on Stock Price: An Empirical Study on Indonesia Stock Exchange - Mulyono Mulyono; Adi Teguh Suprapto; Danang Prihandoko (Bina Nusantara University, 2018)
This research aimed to determine the effect of corporate governance and firm performance on stock prices. It was shown by Corporate Governance Perception Index (CGPI), Return on Assets (ROA), Total Asset Turnover (TATO), and firm size (SIZE) in the Indonesia Stock Exchange (IDX). Data sample used in this research was company listed on IDX during 2009-2012 and participated in CGPI of that period. Financial statement data and stock prices could be obtained from the IDX website and CGPI data were from the Indonesian Institute for Corporate Governance. Hypothesis test used in this research was a multiple linear regression analysis. As a result, the application of corporate governance and ROA give positive but insignificant effect on stock prices. Meanwhile, TATO and SIZE have a positive and significant effect on stock prices. Both variables of corporate governance and firm performance influence stock prices significantly.